Pengaruh Kepercayaan dan Kualitas Pelayanan Terhadap Minat Beli Ulang Melalui Kepuasan Pelanggan Sebagai Variabel Mediasi pada SPBU di Makassar - Rantung, Edmond; Harianto, Eric (Ikatan Da'i Indonesia, 2024)
SPBU 7490210 Galangan Kapal Makassar is a gas station company (Public Fuel Filling Station) established in 2011 and located at Jalan Galangan Kapal No 1, Makassar and is a family business project. This study aims to determine the effect of trust and service quality on customer satisfaction, the effect of customer satisfaction on repurchase interest, and the effect of trust and service quality on repurchase interest on customer satisfaction. The method in this research is quantitative, with analysis using Partial Least Square - Structural Equation Model (PLS-SEM). This study has a sample size of 190 respondents who are customers of the Makassar Shipyard Gas Station who made at least one purchase in the period January 2023 to April 2024. This study shows that trust and service quality have a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on repurchase intention, and trust and service quality have a positive and significant effect on repurchase intention through customer satisfaction as a mediating variable. The implication of this research is that the Public Fuel Filling Station needs to maintain customer satisfaction factors by providing a satisfying experience for customers so that customer satisfaction can increase every time they make a purchase, and provide quality products and good service.